Analysis of the Impact of the Covid-19 Pandemic on Stock Prices in the Construction Sector in Indonesia - Vella Mirfaqoh; Sri Yusriani; Tengku Ahmad Helmi; Ahmad Fadhil; Fajriyah Melati Sholihah; Kusnadi Kusnadi (Greenation Research & Yayasan Global Resarch National, 2023)
The construction sector represents a significant investment choice in the stock market. However, data indicates a decline in the average stock prices of construction sector companies in Indonesia. This study aims to analyze the impact of the Covid-19 pandemic on stock prices in the construction sector in Indonesia and evaluate the sustainability of investing in these stocks. The outbreak of the pandemic has caused significant disruptions and uncertainties in various industries, including construction, making it crucial to understand its effects on stock prices. This study is a quantitative approach and utilizing statistical techniques such as paired sample test and regression analysis. This research finds that all companies in the construction sector have experienced a decrease in stock prices and there is a significant difference in stock prices before and after the pandemic, with the average stock prices being higher before the pandemic conditions. After the pandemic, the data also shows that constrution sector tend to decrease.